FAKTOR PENENTU INTEGRASI PASAR SPASIAL BAWANG MERAH DI INDONESIA - Rahmawati, Astuti; Fariyanti, Anna; Rifin, Amzul (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2019)
This paper is aimedat analyzing determinant factors of spatial market integration at producer level in Indonesia. This study uses secondary data cross-section on the price at producer level.Theproducer marketthat analyzed was 28 provinces of origin and destination of shallotdistribution obtained from the Central Bureau of Statistics publication about Survei Pola Distribusi (POLDIS) Perdagangan Komoditas Bawang merah Indonesia 2015.All data were analyzed using multiple regression analysis. Result of this research shows that factor determiningspatial market integration is total production of destination provinces.